'Brand work': Constructing assemblages in gendered creative labour. (May 2019) - Kivinen, Nina H; Hunter, Carolyn
Recent work has highlighted how brands play an important role within organizational practice. To extend this discussion, we ask: how do gendered media brands come into being in an organization by connecting ideas, objects and people? This article challenges the assumption that brands simply reflect management norms by positioning the brand as an 'assemblage' of multiple connections and linkages, simultaneously shaping and being shaped by those that partake in its production. Employees engage in 'brand work'; that is, the negotiation of the assemblages of the brand in situated and gendered practices. Brand work is explored here in the gendered creative labour of producing girls' magazines. Two studies of pre-teen and teenage girls' magazines in the UK and a Nordic country were analysed in relation to how multiple brand fragments were situated in gendered practices and power relations. Brand work offers an alternative, fragmented perspective to normative forms of control, introducing a simultaneous territorialization and deterritorialization process of stabilization and contestation of the assemblage.